PENGEMBANGAN E-LKPD TEKS NEGOSIASI BERBANTUAN ANYFLIP UNTUK SISWA KELAS X SMA NEGERI 7 MEDAN - Tobing, Jelita; Untung Ritonga, Mara (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop an Anyflip-assisted E-LKPD for negotiation texts for grade X students of SMA Negeri 7 Medan. This study uses a research and development method with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The subjects of this development research were material expert validators, media expert validators, and Indonesian language teachers at SMA Negeri 7 Medan. Data collection techniques were carried out through observation, interviews with Indonesian language teachers, and student needs questionnaires. The results showed that the Anyflip assisted E-LKPD for negotiation texts was declared very suitable for use in learning. The material expert validation obtained a percentage of 83.07% with a very suitable category, the media expert validation obtained a percentage of 93.33% with a very suitable category, and the Indonesian language teacher obtained a percentage of 98.46% with a very suitable category. Therefore, it is concluded that the Anyflip assisted E-LKPD is very suitable for use by teachers and students in learning. Keywords: E-LKPD development, negotiation text, Anyflip, HOTS.